PERLINDUNGAN HUKUM TERHADAP KORBAN CYBER SEXUAL HARASSMENT DALAM MEDIA SOSIAL - Venny Febriyanti Puspita Ningrum; Ufran (Ninety Media Publisher, 2023)
This research aims to comprehend and analyze the legal protections available for victims and the obstacles faced in addressing cases of cyber sexual harassment. The research falls under the category of normative study. The findings reveal that legal protection for victims of cyber sexual harassment is stipulated in Law Number 12 of 2022 concerning Sexual Violence Crimes. This legislation introduces a new approach to providing protection and rights to victims, as outlined in Articles 68 to 70. These articles encompass guarantees for the handling, safeguarding, and recovery of their rights. Obstacles in this context involve the non-seamless implementation of victim rights, which do not always align with expectations. Additionally, the Law on Protection of Witnesses and Victims lacks clear provisions regarding the protection of victims in terms of mental health and social recovery in relation to online sexual harassment.